Direct Numerical Simulation of an Open-Cell Metallic Foam Through Lattice Boltzmann Method (Communications in Computational Physics, 2018)
In this paper Lattice Boltzmann Method (LBM) has been used in order toperform Direct Numerical Simulation (DNS) for porous media analysis. Among thedifferent configurations of porous media, open cell metallic foams are gaining a keyrole for a large number of applications, like heat exchangers for high performancecars or aeronautic components as well. Their structure allows improving heat transferprocess with fruitful advantages for packaging issues and size reduction. In orderto better understand metallic foam capabilities, a random sphere generation code hasbeen implemented and fluid-dynamic simulations have been carried out by meansof a kinetic approach. After having defined a computational domain, the Reynoldsnumber influence has been studied with the aim of characterizing both pressure dropand friction factor throughout a finite foam volume. In order to validate the proposedmodel, a comparison analysis with experimental data has been carried out too.